Teori Konsumsi Islam dalam Peningkatan Ekonomi Umat - febi febi; Abdul Hamid (IAIN Langsa, 2018)
The fulfillment of the needs generally provides an impact or benefits physically and so on. If a requirement sought, then the fulfillment of these needs will provide once public satisfaction, but if the needs weren’t based on the desire, it will only benefit it. There are several mechanisms in the Muslim consumption. Consumption and public satisfaction in Islam do not forbid moslems to fulfill the need or desire for the fulfillment of the human dignity. Indeed everything on this earth destined to humans, but humans are commanded to consume the goods / services that are both lawful and reasonable and not excessive. Fulfillment of desires or needs remain permissible as long as it adds maslahah or does not bring harm. Rational consumer is a smart consumer commodities to determine the benefit of themselves and public interest. The rational consumer’s indicators can be seen among others from their consumption behavior. The explanation highlights the role of consumption are very important as part of national income.